2014
DOI: 10.1111/cobi.12419
|View full text |Cite
|
Sign up to set email alerts
|

Using internet search behavior to assess public awareness of protected wetlands

Abstract: Improving public awareness of protected wetlands facilitates sustainable wetland management, which depends on public participation. One way of gauging public interest is by tracking Internet search behavior (ISB). We assessed public awareness of issues related to protected wetland areas (PWAs) in South Korea by examining the frequencies of specific queries (PWAs, Ramsar, Upo wetland, Sunchon Bay, etc.) using relative search volumes (RSVs) obtained from an Internet search engine. RSV shows how many times a sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The use of Google Trends in this context is well-established (Proulx et al 2014) and has been used to gauge public awareness and interest in a number of other conservation contexts (e.g. Do et al 2014, Nghiem et al 2016, Soriano-Redondo et al 2016, Braczkowski et al 2018. Finally, we used outlier detection in time series analysis to identify (1) monthly peaks in public interest, 2005-2016 and (2) daily peaks in social and editorial media activity and weekly peaks in public interest, 2015-2016 and, for both, assessed temporal co-occurrence amongst datasets and with events.…”
Section: Methodsmentioning
confidence: 99%
“…The use of Google Trends in this context is well-established (Proulx et al 2014) and has been used to gauge public awareness and interest in a number of other conservation contexts (e.g. Do et al 2014, Nghiem et al 2016, Soriano-Redondo et al 2016, Braczkowski et al 2018. Finally, we used outlier detection in time series analysis to identify (1) monthly peaks in public interest, 2005-2016 and (2) daily peaks in social and editorial media activity and weekly peaks in public interest, 2015-2016 and, for both, assessed temporal co-occurrence amongst datasets and with events.…”
Section: Methodsmentioning
confidence: 99%
“…Online information quality (OIQ) 5 Andreassen and Streukens, 2009;Albayrak et al, 2010;Bragazzi, 2014;Do et al, 2015;Evans, 2015 User-friendly accessibility (UFA) 5 Kirakowski et al, 1998;Do et al, 2015 Satisfaction (S) 5 Andreassen and Streukens, 2009;Albayrak et al, 2010;Moore, 2012;Hao et al, 2015 Tourists' behavioral intentions (TBI)…”
Section: Tourist Destination Online Content (Tdoc)mentioning
confidence: 99%
“…For instance, Do et al . () investigated the cultural impact of Ramsar wetland designation in South Korea by tracking relative search volumes (RSVs) of issues related to wetland areas in the country. They found that most internet searches were related to the largest and most well‐known tidal and inland wetlands, and increased substantially after their designation as Ramsar sites in 2008.…”
Section: Advancing Conservation Through Culturomics: Five Key Areasmentioning
confidence: 99%